2018
DOI: 10.1186/s12861-018-0180-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental cycles regulate development time via circadian clock mediated gating of adult emergence

Abstract: BackgroundPrevious studies have implicated a role for circadian clocks in regulating pre-adult development of organisms. Among them two approaches are most notable: 1) use of insects whose clocks have different free-running periods and 2) imposition of artificial selection on either rate of development, timing of emergence or circadian period in laboratory populations. Using these two approaches, influence of clock on rate of development has been elucidated. However, the contribution of circadian clocks in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…That is to say, it is not yet clear whether antibiotics first disturbed eclosion rhythm, then changed microbiota, and finally resulted in obesity or whether the disruptions in microbiota and metabolism occur prior to the alterations in eclosion rhythm. It was previously reported that the pigment-dispersing factor (pdf) and ecdysone-induced protein 74EF ( Eip74EF , also known as E74 ) are essential in controlling eclosion rhythm, , and period (per) and timeless (tim) are core clock genes . Future studies can employ the gal4 -UAS binary system to manipulate gene functions to provide evidence for whether eclosion dysrhythmia is necessary for disturbances on lipid metabolism.…”
Section: Results and Discussionmentioning
confidence: 99%
“…That is to say, it is not yet clear whether antibiotics first disturbed eclosion rhythm, then changed microbiota, and finally resulted in obesity or whether the disruptions in microbiota and metabolism occur prior to the alterations in eclosion rhythm. It was previously reported that the pigment-dispersing factor (pdf) and ecdysone-induced protein 74EF ( Eip74EF , also known as E74 ) are essential in controlling eclosion rhythm, , and period (per) and timeless (tim) are core clock genes . Future studies can employ the gal4 -UAS binary system to manipulate gene functions to provide evidence for whether eclosion dysrhythmia is necessary for disturbances on lipid metabolism.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several earlier studies have shown that pupation is gated in mosquitoes such as Anopheles gambiae 32 and Aedes taeniorhynchus 33 , and is regulated by the duration of the photoperiod via the secretion of the prothoracicotropic hormone that stimulates ecdysone secretion 34 . Also, study showed that importance of the light cycle and the period gene in developmental time memory specifically pupation and adult emergence in fruit flies D. melanogaster is under circadian clock control 35 , 36 . The environmental cycle and period allele both determines the time taken for each pre-adult developmental stages such as time taken for pupation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies have shown that pupation is gated in mosquitoes such as Anopheles gambiae [34] and Aedes taeniorhynchus [35], and is regulated by the duration of the photoperiod via the secretion of the prothoracicotropic hormone that stimulates ecdysone secretion [36]. Also, it showed that importance of the light cycle and the period gene in developmental time memory specifically pupation and adult emergence in fruit flies D. melanogaster is under circadian clock control [37,38]. The environmental factors with circadian clock (eg: light input pathways regulate the period gene expression) determines the stage of development and duration of time (width of the gate) within a cycle available for an insect to emerge into an adult [39].…”
Section: Discussionmentioning
confidence: 99%